Actin-Dependent Alterations of Dendritic Spine Morphology in Shankopathies. (4th October 2016) - Sarowar, Tasnuva; Grabrucker, Andreas M.
Abstract : Shank proteins (Shank1, Shank2, and Shank3) act as scaffolding molecules in the postsynaptic density of many excitatory neurons. Mutations in SHANK genes, in particular SHANK2 and SHANK3, lead to autism spectrum disorders (ASD) in both human and mouse models. Shank3 proteins are made of several domains—the Shank/ProSAP N-terminal (SPN) domain, ankyrin repeats, SH3 domain, PDZ domain, a proline-rich region, and the sterile alpha motif (SAM) domain. Via various binding partners of these domains, Shank3 is able to bind and interact with a wide range of proteins including modulators of small GTPases such as RICH2, a RhoGAP protein, and β PIX, a RhoGEF protein for Rac1 and Cdc42, actin binding proteins and actin modulators. Dysregulation of all isoforms of Shank proteins, but especially Shank3, leads to alterations in spine morphogenesis, shape, and activity of the synapse via altering actin dynamics. Therefore, here, we highlight the role of Shank proteins as modulators of small GTPases and, ultimately, actin dynamics, as found in multiple in vitro and in vivo models. The failure to mediate this regulatory role might present a shared mechanism in the pathophysiology of autism-associated mutations, which leads to dysregulation of spine morphogenesis and synaptic signaling.